Study at home during the covid-19 pandemic as a legal protection for children's rights in Indonesia - Ratri Novita Erdianti; Nur Putri Hidayah (Legality : Jurnal Ilmiah Hukum, 2020)
The application of the online learning system during the COVID-19 pandemic has caused problems related to learning methods that require adequate facilities that not all students have. In addition, the community also feels that this method is not optimal for students, especially elementary school students who find it difficult to accept online learning which also due to heaps of works to replace the material students can use. The purpose of this paper is to see that the study at the home policy is the right government action to take in accordance with the legal protection mandated by Law No. 35 of 2014 concerning Amendments to Law No. 23 of 2002 concerning Child Protection to continue on carrying out the learning process so that the world of education is not paralyzed due to the spread of COVID-19. The purpose of this study is to examine the study at the home policy as a guarantee of legal protection mandated by Law No. 35 of 2014 concerning Amendments to Law No. 23 of 2002 concerning Child Protection. The method used in this study is the normative method. The outcomes show that online learning policies are the best solution and are in line with the principles of legal protection for children's rights in Indonesia, especially regarding the right to be safe from harm, to be kept away from disease, and the right to live and develop.